Numerical Research of the Submerged High-Pressure Cavitation Water Jet Based on the RANS-LES Hybrid Model. (12th July 2021) - Yang, Yongfei; Shi, Weidong; Tan, Linwei; Li, Wei; Chen, Songping; Pan, Bo
Abstract : The submerged high-pressure water jet has the characteristics of high velocity, strong turbulence, and severe cavitation. In order to reveal the formation mechanism of shear cavitation in the submerged high-pressure water jet and to grasp the turbulent structure and velocity distribution characteristics in the jet, the prediction ability of different turbulence models is studied first. The models represent the RANS model and RANS-LES hybrid model which are used to simulate the same cavitation jet, and the results are compared with the experimental results. The most reasonable model is then used to investigate the submerged high-pressure cavitation jet with different cavitation numbers. It is found that the calculation accuracy for small-scale vortexes has a great influence on the prediction accuracy of cavitation in the submerged jet. Both the DDES model and the SBES model can effectively capture the vortexes in the shear layer, and the SBES model can obtain more turbulence details. The result of the simulation under different cavitation numbers using the SBES model agrees well with the experimental result. Under the condition with low cavitation number, an intensive shear layer is formed at the exit of the nozzle, and small-scale vortexes are distributed along the shear layer. Mass transfer rate is relatively high in the region with a stronger vortex, which confirms that the low pressure in the vortex center is the main reason for the generation of cavitation in the shear layer. With the decrease of the cavitation number, the cavitation intensity increases obviously, while the nondimensional velocity along the radial direction changes little, which follows an exponential function.